Multi‐Foci Metalenses: A Multi‐Foci Metalens with Polarization‐Rotated Focal Points. Issue 12 (10th December 2019) - Zang, Xiaofei; Ding, Hongzhen; Intaravanne, Yuttana; Chen, Lin; Peng, Yan; Xie, Jingya; Ke, Qinghong; Balakin, Alexey V.; Shkurinov, Alexander P.; Chen, Xianzhong; Zhu, Yiming; Zhuang, Songlin
Abstract : Driven by system integration and device miniaturization, a single device with multiple functions is desirable. In article number 1900182, Xianzhong Chen, Yiming Zhu, and co‐workers demonstrate a metalens that can focus the incident THz waves into two focal spots with predesigned polarization rotation. This approach not only provides a platform for multiplexing of focusing and polarization rotation, but also opens a novel avenue for polarization‐dependent imaging.